Love For Sale: Virtual Lovers Rental Services in Indonesia - Louwbry, Anastasya; Girsang, Lasmery RM (Lingkar Studi Komunikasi (LISKI), 2024)
The way interpersonal relationships, particularly romantic ones, are formed has gradually transitioned to the virtual realm. Digital communication media now serve as platforms where users can meet and establish relationships without the constraints of physical distance and face-to-face interactions. The phenomenon of Virtual Lovers, originating in China, explains how individuals offer services as virtual partners to accompany clients. This relationship can be understood through the concept of Mediated Relationship, where romantic relationships flourish without contextual limitations, using digital communication as the primary medium. This study aims to explore the virtual communication process and interpersonal relationships of a Virtual Lover in their profession. Using a constructivist paradigm and a qualitative approach, this study aims to examine the experiences and values of Virtual Lovers in situational romantic interactions with their clients. It was found that a Virtual Lover communicates with their client in a situational romantic relationship, engaging in conversations or sharing stories about life’s problems. Virtual Lovers create a self-profile reflecting how they wish to be perceived through virtual communication. This exchange of information builds familiarity and trust as their knowledge of each other deepens. Despite not meeting face-to-face, Virtual Lovers feel their persona as a talent is distinct from their real-life self, where talent must listen attentively and adapt to the needs of their clients. Agencies acting as intermediaries between clients and talents enforce various regulations to protect the privacy and security of all parties involved.